Getting to grips with the public trust doctrine in biodiversity conservation: A brief overview - Andrew C. Blackmore (Bothalia: African Biodiversity & Conservation, 2018)
The explicit incorporation of the public trust doctrine into South Africa’s Bill of Rights in South Africa’s Constitution, and its subsequent codification into the country’s environmental biodiversity, protected area, water, minerals and heritage legislation, occurred to a large extent without applause or fanfare. It is apparent that in the 20-odd years since the adoption of South Africa’s Constitution, the existence and importance of the public trust doctrine within the academic and legal fraternities, bureaucratic decision-making and the courts have largely been overlooked. This observation evokes curiosity about the history and evolution of the doctrine and its meaning and relevance in, at least, the conservation of biodiversity in a South African context. It is concluded that the nature of the application of the public trust doctrine in South Africa remains an enigma, and the development and refinement of this jurisprudence are required. The variable and, in places, conflicting wording of the trust-related provisions in a number of South Africa’s environmental statutes suggests that the doctrine and hence the nature of its application was not fully understood by the drafters of the statutes or by the legislature adopting those statutes into law. The public trust doctrine in South African environmental law lies beyond the country’s Constitution, and appears to have multiple bloodlines, which dispels the notion that South Africa hermetically imported the concept from a single source. The interpretation and hence the nature of the application of the doctrine in South Africa is likely to be influenced by the country’s heritage and hence is likely to vary between the disciplines that constitute South Africa’s environmental law.